Closure of Educational Institutes Due to Coronavirus Outbreak (COVID-19): Its Impact on Education Process and Mental Health of Students and Academician - Sahoo, Manoj Kumar; Sahoo, Limali (International Journal of Recent Advances in Engineering and Technology, 2021)
Currently, we are facing the danger of the COVID-19, which is started from Wuhan city, China, and speeding like bush fire in the jungle, it covers the different regions of the globe. The COVID-19 is epidemic a pandemic being declared by the WHO (World Health Organization), its effects on the day to day work in the Government as well as the private business and economics sector, and social and public events, as well as in the education. The progressive and development work is forced to suspend or stopped due to the COVID-19 throughout the globe. The lockdown process effect on the regular activity of the educational institutes like examinations, workshops, conferences either forced canceled or suspended. The Government, the Universities, and the policymaker body for education across the globe monitor the system. In this paper we like to address the problem arise, policy and the effective solution can or need to take in considering the education and physical as well as mental health of the students, faculty, and staff involving this process.